Establishing a small and successful dating service on the internet. - Chan, Wai Keng. (2009)
This paper examines the opportunities and pitfalls of setting up a small business on the Internet. It gives a full report on the business planning, implementation and promotion of a small, online dating service company, Strictly Singles.